Perilaku Peserta Didik Dalam Lembaga Pendidikan Islam - Ahmad Salim Ulul Albaab; Titin Nurhidayati; M. Ilham Fikron; Mohammad Futuh Muafi; M abdullah viki; Sayyid Abdullah (4, 2026)
Student behavior is a key indicator of the success of the educational process, particularly in Islamic educational institutions based on the values ​​of the Qur'an and Sunnah. From the perspective of Islamic educational psychology, student behavior is not understood solely as an outward response, but rather as a manifestation of the integration of human innate potential, the educational process undertaken, and the influence of the social and spiritual environment. Every student inherently possesses an innate desire for good deeds, which needs to be guided and developed through holistic and continuous education. Islamic educational psychology views student behavior as influenced by various factors, both internal and external. Internal factors include the student's faith, motivation, psychological readiness, and spiritual awareness. Meanwhile, external factors include the role of educators, the family environment, school culture, and the educational methods applied. In Islamic educational institutions, educators hold a strategic position as role models (uswah hasanah) who not only transfer knowledge but also instill values ​​and guide the formation of morals. A religious and conducive educational environment plays a significant role in shaping student behavior. Through the practice of worship, discipline, and social interaction based on Islamic values, students are trained to internalize religious teachings in their daily lives. Consistent and sustainable habituation methods are an effective means of shaping positive character and behavior. The literature review indicates that the internalization of spiritual values, the role models of educators, and the religious culture of educational institutions are dominant factors in shaping student behavior. Thus, Islamic education plays a strategic role in producing a generation of faith, noble character, discipline, and responsibility, in line with the primary goals of Islamic education itself. Abstrak Perilaku peserta didik merupakan indikator utama keberhasilan proses pendidikan, terutama dalam lembaga pendidikan Islam yang berlandaskan nilai-nilai Al-Qur’an dan Sunnah. Dalam perspektif psikologi pendidikan Islam, perilaku peserta didik tidak dipahami semata-mata sebagai respons lahiriah, melainkan sebagai manifestasi integrasi antara potensi fitrah manusia, proses pendidikan yang dijalani, serta pengaruh lingkungan sosial dan spiritual. Setiap peserta didik pada dasarnya memiliki fitrah untuk berbuat baik, yang perlu diarahkan dan dikembangkan melalui pendidikan yang holistik dan berkesinambungan. Pendidikan psikologi Islam memandang bahwa perilaku peserta didik dipengaruhi oleh berbagai faktor, baik internal maupun eksternal. Faktor internal meliputi keimanan, motivasi, kesiapan psikologis, dan kesadaran spiritual peserta didik. Sementara itu, faktor eksternal mencakup peran pendidik, lingkungan keluarga, budaya sekolah, serta metode pendidikan yang diterapkan. Dalam lembaga pendidikan Islam, pendidik memiliki posisi strategis sebagai teladan (uswah hasanah) yang tidak hanya mentransfer ilmu pengetahuan, tetapi juga menanamkan nilai dan membimbing pembentukan akhlak. Lingkungan pendidikan yang religius dan kondusif turut berperan besar dalam membentuk perilaku peserta didik. Melalui pembiasaan ibadah, disiplin, serta interaksi sosial yang berlandaskan nilai-nilai Islam, peserta didik dilatih untuk menginternalisasi ajaran agama dalam kehidupan sehari-hari. Metode pembiasaan yang konsisten dan berkelanjutan menjadi sarana efektif dalam membentuk karakter dan perilaku positif. Hasil kajian pustaka menunjukkan bahwa internalisasi nilai spiritual, keteladanan pendidik, dan budaya religius lembaga pendidikan merupakan faktor dominan dalam membentuk perilaku peserta didik. Dengan demikian, pendidikan Islam memiliki peran strategis dalam melahirkan generasi yang beriman, berakhlak mulia, disiplin, dan bertanggung jawab, sejalan dengan tujuan utama pendidikan Islam itu sendiri.